Small-Molecule Inhibitors of the Receptor Tyrosine Kinases: Promising Tools for Targeted Cancer Therapies - Hojjat-Farsangi, Mohammad (MDPI, 2014)
Chemotherapeutic and cytotoxic drugs are widely used in the treatment of cancer. In spite of the improvements in the life quality of patients, their effectiveness is compromised by several disadvantages. This represents a demand for developing new effective strategies with focusing on tumor cells and minimum side effects. Targeted cancer therapies and personalized medicine have been defined as a new type of emerging treatments. Small molecule inhibitors (SMIs) are among the most effective drugs for targeted cancer therapy. The growing number of approved SMIs of receptor tyrosine kinases (RTKs) i.e., tyrosine kinase inhibitors (TKIs) in the clinical oncology imply the increasing attention and application of these therapeutic tools. Most of the current approved RTK–TKIs in preclinical and clinical settings are multi-targeted inhibitors with several side effects. Only a few specific/selective RTK–TKIs have been developed for the treatment of cancer patients. Specific/selective RTK–TKIs have shown less deleterious effects compared to multi-targeted inhibitors. This review intends to highlight the importance of specific/selective TKIs for future development with less side effects and more manageable agents. This article provides an overview of: (1) the characteristics and function of RTKs and TKIs; (2) the recent advances in the improvement of specific/selective RTK–TKIs in preclinical or clinical settings; and (3) emerging RTKs for targeted cancer therapies by TKIs.